Introduction : from the "new ecology" to the new ecologies. - Biersack, Aletta (American Antropological Association, 1999)
An earlier ecological anthropology defined its project within the compass of the idealism v. materialism debate. Culture was an adaptive tool, instrumental rather than formal; it was intelligible with respect to its material effects, notÑas the idealists would maintainÑin terms of itself, as an autonomous, self-determining order of reality. This argument was mounted with respect to bounded, stable, self-regulating, local, or at best regional entities and the environment they inhabited. All of the premises of the earlier ecology have since been challenged, and today's ecologiesÑsymbolic, historical, and politicalÑradically depart from the reductions and elisions of the ecological anthropology of the past. In particular, the new ecologies override the dichotomies that informed and enlivened the debates of the pastÑnature/culture, idealism/materialismÑand they are informed by the literature on transnationalist flows and local-global articulations. This introduction positions Rappaport's work within this historical shift from a polarized field of mutually exclusive frameworks to today's synthetic new ecologies and their antireductive materialism. Rappaport's work, produced over three decades, serves, in and through its own transformations, as a bridge between the reductive materialism of the past and a new-materialist ecology.